Sovereign Risk, European Crisis-Resolution Policies, and Bond Spreads - Juha Kilponen; Helinä Laakkonen; Jouko Vilmunen (Association of the International Journal of Central Banking, 2025)
We study the effects of a wide range of European crisis resolution policies, including large-scale asset purchase programs of the ECB, on ten-year sovereign bond spreads of seven European countries. Our results based on daily data on bond spreads suggest that policies that are directly geared towards easing the funding strains of the sovereigns and improving market liquidity have been most effective in calming the European sovereign markets. Quantitatively the largest effects on bond spreads are due to announcements of ECB’s SMP program and OMTs. At the same time, announcements of financial assistance programs have typically increased somewhat the perceived riskiness of long-term bonds in the guarantor countries but reduced the bond spreads in the countries receiving funding.